2015
DOI: 10.1371/journal.pone.0120724
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Expression of Heat-Shock Protein 27 Is Associated with Worse Clinical Outcome in Patients with Colorectal Cancer Lung Metastases

Abstract: BackgroundPulmonary metastases are common in patients with primary colorectal cancer (CRC). Heat-shock protein 27 (Hsp27) is upregulated in activated fibroblasts during wound healing and systemically elevated in various diseases. Cancer-associated fibroblasts (CAFs) are also thought to play a role as prognostic and predictive markers in various malignancies including CRC. Surprisingly, the expression of Hsp27 has never been assessed in CAFs. Therefore we aimed to investigate the expression level of Hsp27 in CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…Interestingly, we found that α-SMA + cells, including smooth muscle cells and myofibroblasts, were the cells that showed the highest levels of phosphorylated Hsp27 both in the normal mucosa and tumors, and that this property was dependent on MK2 expression. This is consistent to previous reports on the expression pattern of Hsp27 in CRC, as well as its coexpression with α-SMA in CRC lung metastases (32). Interestingly, phosphorylation of Hsp27, which is increased in blood endothelial cells, is not influenced by MK2 deletion, which indicates that the function of the p38/ MK2/Hsp27 pathway is cell and tissue dependent.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, we found that α-SMA + cells, including smooth muscle cells and myofibroblasts, were the cells that showed the highest levels of phosphorylated Hsp27 both in the normal mucosa and tumors, and that this property was dependent on MK2 expression. This is consistent to previous reports on the expression pattern of Hsp27 in CRC, as well as its coexpression with α-SMA in CRC lung metastases (32). Interestingly, phosphorylation of Hsp27, which is increased in blood endothelial cells, is not influenced by MK2 deletion, which indicates that the function of the p38/ MK2/Hsp27 pathway is cell and tissue dependent.…”
Section: Discussionsupporting
confidence: 92%
“…5F). In agreement with these data, staining with antibodies against phospho-Hsp27 has revealed a stromal pattern of Hsp27 activation in human tumors (32). These results indicate that MK2 regulates activation of Hsp27 in intestinal mesenchymal cells, both in homeostasis and cancer in the intestine.…”
Section: Mk2 In Intestinal Epithelial and Endothelial Cells Contributsupporting
confidence: 82%
“…At sufficient levels, HspB1 has been widely considered to serve multiple protective functions, but its overabundance may protect mutant cells from programmed death or even lead to cancer. A previous study associated stromal expression of HspB1 (Hsp27) with cancer development (Schweiger et al 2015). Some researchers believe that inappropriate expression of Hsps, especially HspB1, can block apoptosis pathways and actively be involved in various processes such as tumor cell proliferation, invasion, metastases, and death (Lianos et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other functions of HSP27 include direct interference with apoptotic pathway and regulation of cytoskeleton dynamics [15,16]. Whereas its primary function is to promote cellular homeostasis under stressor conditions, overexpression of HSP27 is closely related to tumorigenesis, metastasis, and invasiveness in various cancers such as head and neck squamous cell carcinoma, pediatric acute myeloid leukemia, breast cancer, and colorectal cancer [17][18][19][20]. HSP27 has been identified as an important regulator of the Salvador-Warts-Hippo pathway (Hippo pathway), which controls tumor initiation, progression, cancer stem cell programming, and metastasis.…”
Section: Role Of Hsp27 As An Upstream Regulator Of Oncogenic Pathwaysmentioning
confidence: 99%